Relationship between Nutritional Status and Development of Preschool Aged Children in the Operational Area of Puskesmas Batua Raya - Azizah, Nuraeni; Darmawansyih; Fauziah, Henny (Fakultas Kedokteran Universitas Muslim Indonesia, 2021)
Introduction: Development is a mental change that occurs gradually and over time, starting from simple abilities to more difficult abilities, such as attitude, behavior and intelligence. Preschool age is a golden age in which all aspects of development play an important role in aspects of further development. The study aimed to determine the relationship between nutritional status and development of preschool aged children in the operational area of ​​Puskesmas Batua Raya. Methods: The study used a cross sectional study design with total sample of 196 respondents. Data were collected through anthropometric measurements of body weight and KPSP assessment (developmental pre-screening questionnaire) was carried out. Data analysis was performed using the chi square test. Results: Results of the study found that children with appropriate development were higher in good nutritional status (74%) than those who were below the nutritional status (5.6%). Analysis of the two variables shows the value of p = 0.000. Statistically, there was a significant relationship between nutritional status and development of preschool children. Conclusion: Based on the research, it may be concluded that there is a relationship between maternal knowledge and the behavior of exclusive breastfeeding in the operational area of the Sudiang Primary Health Center.